Impact of Supplementation on Anemia, Cognition, and Growth in Children: A Scoping Review of Randomized Controlled Trials - Dafa Bintang Nugroho; Anjani Nelka Rachmawatty; Almira Sitasari; Agus Wijanarka; Tri Siswati (Knowledge Dynamics, 2024)
Background: Anemia in children is a global health problem that can affect their cognitive and physical development. Various supplementation interventions have been used to treat anemia, including iron, folic acid, vitamins, and other minerals. Although some studies have shown improvements in anemia status, challenges in adherence to treatment and side effects remain barriers. Objective: This scoping review aims to map the available scientific evidence related to interventions and supplementation in children with anemia. This study identifies the types of interventions used, the target population, and the outcomes reported in the studies. Methods: A literature search was conducted through PubMed and Google Scholar with the keywords